Reported traffic injuries during a pilot of injury surveillance system in Kingdom of Saudi Arabia - Faisal Murdhi Alanazi (19774341) (2015)
Road traffic injuries are second leading cause of mortality in hospitals of Ministry of Health (MOH) – Kingdom of Saudi Arabia (KSA) (1), costing billions of Saudi Riyals annually (2). The Injury & Accidents Prevention Program in MOH, realizing the dearth of data about injuries, designed a uniform Injury Surveillance System in 2013, with assistance of the World Health Organization (WHO) and in collaboration with Ministry of Interior and Red Crescent. The Injury Surveillance System aimed to gather regular ongoing information for prevention and control of injuries and efficient use of resources. The pilot phase involved a multistage stratified random sample, where half of 20 health regions were selected in first stage and 14 health facilities from each region in second stage stratified by type and level of facility. A minimum of two physicians from each selected health facility were trained on the predesigned tool, adopted and modified from WHO-CDC Guidelines (3), before the start of data collection. The data on the prescribed form was collected at the healthcare facilities and communicated through Regional Coordinator to the Injury & Accident Prevention Program in MOH on regularly basis for entry and analysis. Injuries were third highest cases (15%) after falls (31%) and blunt force (20%) among the 10,008 reported cases. About 32% of drivers were reported to be over-speeding; in 13.7%, condition of vehicle was flawed; and some 13 % crashes seemingly occurred due to bad weather. The pilot identified that data from health facilities is very useful for decision making. Surveillance system is efficient and has the capacity to capture injury cases reporting to health facilities, but necessitates the inclusion of nurses and paramedics besides the attending physicians, to distribute the work load. Robust functioning of the system would require more ownership of the regional offices, besides continuous commitment of senior management at MOH. Other Information Published in: Journal of Local and Global Health Science, title discontinued as of (2017) License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.5339/jlghs.2015.itma.14